One new genus and species of Typhlocybini (Hemiptera: Cicadellidae: Typhlocybinae) from China - Li, Mengyang; Cao, Yanghui (Zootaxa, 2026)
A remarkable new genus of the leafhopper tribe Typhlocybini with significantly elongated style, Prodorsostyla gen. nov., is described based on a new species P. jinzishiensis sp. nov. found on Cinnamomum camphora from China. Habitus photos of the new species and its host plant as well as the photos of the male genitalia are provided.